2002
DOI: 10.1603/0022-2585-39.5.777
|View full text |Cite
|
Sign up to set email alerts
|

Host-Feeding Habits ofCulexand Other Mosquitoes (Diptera: Culicidae) in the Borough of Queens in New York City, with Characters and Techniques for Identification ofCulexMosquitoes

Abstract: The host-feeding patterns of mosquitoes (n = 247) collected in the Borough of Queens in New York City in July and August 2000 were investigated using an indirect ELISA and a polymerase chain reaction (PCR)-heteroduplex assay. Culex pipiens L. and Cx. restuans Theobald fed primarily on birds, and their feeding habits support their implication as enzootic vectors of West Nile virus. Culex salinarius Coquillett and Coquillettidia perturbans (Walker) fed mainly on mammals, with fewer blood meals taken from birds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
164
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 27 publications
12
164
0
3
Order By: Relevance
“…restuans ; all analyzed blood meals were from avian species. These findings were consistent with prior host preference studies ( 8 , 9 , 16 , 20 ) and strongly support the view that this predominant "early season" species is most likely involved in initiation and amplification of WNV transmission among wild birds and rarely, if ever, feeds on humans in this region. This finding differs from a recent blood-meal analysis by Gingrich and Williams ( 19 ), who found that a limited number (n = 9) of Cx.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…restuans ; all analyzed blood meals were from avian species. These findings were consistent with prior host preference studies ( 8 , 9 , 16 , 20 ) and strongly support the view that this predominant "early season" species is most likely involved in initiation and amplification of WNV transmission among wild birds and rarely, if ever, feeds on humans in this region. This finding differs from a recent blood-meal analysis by Gingrich and Williams ( 19 ), who found that a limited number (n = 9) of Cx.…”
Section: Discussionsupporting
confidence: 91%
“…restuans are largely ornithophilic, whereas Cx. salinarius feeds more frequently on mammals ( 8 ), which supports the idea of a "bridge vector" role for this species. Nevertheless, collections from New Jersey indicate that mosquitoes of the Cx.…”
supporting
confidence: 64%
See 3 more Smart Citations